Common object request broker architecture (CORBA)-based security services for the Virtual Radiology Environment - Martinez, Ralph (Springer-Verlag, 2000)
The US Army Great Plains Regional Medical Command (GPRMC) has a requirement to conform to Department of Defense (DoD) and Army security policies for the Virtual Radiology Environment (VRE) Project. Within the DoD, security policy is defined as the set of laws, rules, and practices that regulate how an organization manages, protects, and distributes sensitive information. Security policy in the DoD is described by the Trusted Computer System Evaluation Criteria (TCSEC), Army Regulation (AR) 380-19, Defense Information Infrastructure Common Operating Environment (DII COE), Military Health Services System Automated Information Systems Security Policy Manual, and National Computer Security Center-TG-005, “Trusted Network Interpretation.” These documents were used to develop a security policy that defines information protection requirements that are made with respect to those laws, rules, and practices that are required to protect the information stored and processed in the VREProject. The goal of the security policy is to provide, for a C2-level of information protection while also satisfying the functional needs of the GPRMC’s user community. This report summarizes the security policy for the VRE and defines the CORBA security services that satisfy the policy. In the VRE, the information to be protected is embedded into three major information components: (1) Patient information consists of Digital Imaging and Communications in Medicine (DICOM)-formatted fields. The patients information resides in the digital imaging network picture archiving and communication system (DIN-PACS) networks in the database archive systems and includes (a) patient demographics; (b) patient images from x-ray, computed tomography (CT), magnetic resonance imaging (MRI), and ultrasound (US); and (c) prior patient images and related patient history. (2) Meta-Manager information to be protected consists of several data objects. This information is distributed to the Meta-Manager nodes and includes (a) radiologist schedules; (b) modality worklists; (c) routed case information; (d) DIN-PACS and Composite Health Care system (CHCS), messages, and Meta-Manager administrative and security information; and (e) patient case information. (3) Access control and communications security is required in the VRE to control who uses the VRE and Meta-Manager facilities and to secure the messages between VRE components. The CORBA Security Service Specification version 1.5 is designed to allow up to TCSEC’s B2-level security for distributed objects. The CORBA Security Service Specification defines the functionality of several security features: identification and authentication, authorization and access control, security auditing, communication security, nonrepudiation, and security administration. This report describes the enhanced security features for the VRE and their implementation using commercial CORBA Security Service software products.